Reactions to and explanations for the birth of a baby with albinism: a qualitative study in Busoga, Uganda - Julie Taylor; C Bradbury-Jones; Peter Ogik; Fazira Kawuma; Jane Betts; Patricia Lund (BMJ Open)
Objectives Babies born with the genetic condition albinism lack pigment in their hair, skin and eyes due to compromised melanin production. This leads to poor vision and the risk of early death due to skin cancer. In Uganda, one of the least developed countries in the world, their lack of pigmentation makes them very different in appearance within their communities. Local explanations of albinism include links to witchcraft and the supernatural. We aimed to explore reactions to the birth of a baby with albinism in Uganda.Design Secondary analysis of birth stories derived from qualitative interviews and focus group discussions in sharing circles.Setting Interviews took place in the Busoga subregion (kingdom) in the eastern part of Uganda.Participants Seventy-three (73) participants took part in eight sharing circles (n=56) and 17 individual interviews. Participants included people with albinism, parents of people with albinism and a range of other interested parties, including local leaders and teachers.Results Reactions were generally those of shock and rejection, although cases of acceptance were also recorded. The varied explanations given to account for this unexpected event included accounts involving witchcraft, ghosts, animal familiars and religion, as well as genetics. In a framework surmising that someone must possess a dark skin to be intrinsically valued in African societies a baby with albinism does not fulfil this requirement of ‘personhood’. The mother was often blamed for having produced some ‘thing’ that is not a proper person.Conclusions We argue that a biomedical explanation, although unlikely to displace other understandings, helps to establish a baby with albinism as a real person with a genetic difference, and hence fosters greater acceptance.